Globalization and income inequality in developing economies: A comprehensive analysis - Mosab I. Tabash; Yasmeen Elsantil; Abdullah Hamadi; Krzysztof Drachal (Economies, 2023)
Around the world, people are becoming more and more worried about how globalization will affect their standard of living. According to the literature, globalization has resulted in the marginalization of the impoverished populations in developing economies and has exacerbated inequality, while the opposite may also be true. The objective of this study is to investigate the impact of globalization on income inequality. The study used two-stage least squares (2SLS) to study the influence of globalization on income inequality in 18 developing countries from 1991-2021. Utilizing the KOF index of globalization, it is determined that globalization, together with its three aspects, has a negative effect on income inequality among developing economies. Evidence demonstrates that the combination of trade openness and foreign direct investment (FDI) plays a significant role in reducing inequality among developing economies. We recommend developing economies actively support globalization in terms of trade and FDI in accordance with the findings. By expanding trade opportunities and opening up markets, globalization can benefit developing nations. This may result in a rise in FDI, the creation of jobs, and technological developments. Governments can contribute to raising the living standards of their inhabitants, lowering rates of poverty, and closing the income gap by promoting globalization. Although the study emphasizes the well-established link between globalization and income inequality, it focuses on the effects of various globalization dimensions, emphasizing the need to comprehend how different dimensions of globalization, namely economic, political, and social globalization affects inequality in developing economies.
Keywords: C26; D63; F4; 330; developing economies; globalization; income equality; 2SLS